Geological and geomorphological influences on a recent debris flow event in the Ice-scoured Mountain Quaternary domain, western Scotland. Issue 4 (August 2021) - Palamakumbura, Romesh; Finlayson, Andrew; Ciurean, Roxana; Nedumpallile-Vasu, Nikhil; Freeborough, Katy; Dashwood, Claire
Abstract: Debris flows in settings that have experienced net glacial erosion within the UK's Ice-scoured Quaternary domain are the result of a complex interaction of a range of geological and geomorphological factors. On the 11 th of August 2016 a rainfall-triggered debris flow deposited 100 t of sediment onto local road and rail infrastructure blocking transport between town of Fort William and port of Mallaig in north-west Scotland. The debris flow occurred in an ice-scoured setting, where current 1:50, 000-scale geological maps suggest that little or no sediment is expected on the valley slopes. In this study, we show how weathering and mass-wasting processes have interacted with bedrock structures to fill localised depressions with sediment on the upper parts of the slope. The intense rainfall event of August 2016 caused the destabilisation of this localised sediment, with eventual failure along bedrock joint surfaces resulting in two debris flows. This study demonstrates the combination of processes that can result in thick accumulations of sediment on slopes that are otherwise generally lacking in superficial sediment cover. These sediment accumulations have the potential to pose a significant landslide hazard in areas that might previously have been thought of as lower susceptibility. The research illustrates a need to improve understanding and representation of sediment thickness and distribution on hill slopes – particularly those that show an absence of superficial deposits at the scale of currently available geological maps.